At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
Can someone please walk me through how to do this
first equation times 3 and second equation times -2 (2x + 2y = 6) × 3 (x + 3y = −1) × (-2) this will get you a new (but equivalent to the previous) system of equations. 6x + 6y = 18 -2x - 6y = 2 now add the equations and solve for x
So you just take one of the equations and multiply it to the other equation?
first equation divide each term by 2
Would it be x+y=6 then?
I didnàt multiply equation times equation, all I did is that I multiplied each term in the equation times some number.... i did this for both of the equations, and choose the numbers by which to multiply in a way that would eliminate the y (since the variable you need is x).
So you would come up with 6x+6y= 18? for the first equation and -2x+-6=2?
-2x - 6y = 2 for the second equation, you meant (right ?)
Sorry yes thats what I meant
yes, that is what you inded come up with.
Now, add the equations
6x + 6y = 18 -2x - 6y = 2
Okay so it would be 4x + 18y = 20?
Oh wait 12y*
no, not 12. when you add 6 and -6 you get 6+(-6)=6-6=0 and so when you add 6y and -6y you get (6y)+(-6y)=??
Oh so it would be 4x = 20?
so x is?
yes, that is correct!
Thank you so much! That makes a lot more sense now!
very nice to hear that... you are welcome!